Transfer of Foster Parents' Assets to Foster Children from the Perspective of Islamic Law - Azuratunnasuha, Azuratunnasuha (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study Families that do not have children, not a few who do childcare or adoption. The child being cared for can be from a close family or from someone else Methodology: This research uses the literature study method which relies on bibliographic sources from books and articles in scientific journals related to the subject matter, reading data with the thoughts of experts with a constructive approach and interpretation of the main content Main Findings: voluntary legal action, which is based on the free will of the testator as the owner of the property. However, based on the word of Allah surah al-Baqarah (2) verse 180, the will law is obligatory, namely to give a share to parents or relatives who do not receive the inheritance because they are hijab (mahjub), or cannot become heirs because they are obstructed (mamnu). Novelty/Originality of this study: The inheritance which was carried out in Gajah village, Ngoro sub-district, Jombang Regency, did not have a clear basis, namely regarding which legal options would be used in the distribution of the inheritance, or who should be the heirs and those who are entitled to inheritance.